PENGARUH PROBLEM BASED INSTRUCTION TERHADAP KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA KELAS X SMA NEGERI KABUPATEN PESISIR SELATAN - Okviani Syafti (STKIP Pesisir Selatan, 2016)
This research is aimed to reveal the effect of PBI models in students ability in mathematical creative thinking students ability started from high, medium and low, as well as the interaction between the model and the learning ability of students in influencing early mathematical creative thinking.This research is a quasi experimental design of The Randomized Posttest Only Control Group Design. The population in this research is all students of class X SMAN Pesisir Selatan. The sampling technique used is Random Sampling. Samples of this research are the students of class X SMAN 2 Lengayang in the class X.4 as the experimental class and class X.1 as the control class. The instrument used is a test consists of beginning capabilities test and Posttest to see the students' mathematical creative thinking ability. Data analysis was performed using t-test and ANAVA two ways for interaction. There are some conclusions that can be acquired based on the results of research and discussion. First, the students which use PBI have higher mathematical creative thinking ability than students that use the conventional learning. Second, mathematical creative thinking high ability students that using PBI model of learning higher than students using the conventional learning.Third, the starting studentscreative thinking ability is medium and the students which use PBI higher than students using conventional learning. Fourth, the mathematical ability to think creatively mathematical learners PBI higher than students who use conventional learning.Fifth, there is no interaction between the model of learning and the prior knowledge of students in influencing the students mathematical creative thinking.